OP0293-PARE Problems, goals and urgent wishes of young austrians diagnosed with rheumatic disorders: a report. (12th June 2018) - Wegscheider, P.; Schaffer, G.
Abstract : Background: The Austrian Rheumatism League provides information about rheumatic disorders in order to improve the quality of life. It helps to get in contact with professional health caregivers and supports the sharing of personal experience. Because we suspected that young patients often have very different problems, goals and urgent wishes than their older counterparts, we conducted a survey addressing these questions. Objectives: We sent a questionnaire to young people between 15 and 35 years old diagnosed with 'rheumatism' and in order to get information about their diagnosis, their daily lives, their problems, goals and urgent wishes. Methods: 52 persons between 15 and 35 years old and diagnosed with juvenile idiopathic arthritis, rheumatoid arthritis, psoriatic arthritis, Mb. Bechterew, systemic lupus erythematodes, Sjögren-Syndrome, Sharp-Syndrome or fibromyalgia filled out a questionnaire. The subjects were divided into two groups (15–25, 25–35 years). The questions covered gender, province of residence, education, job, retirement, pregnancies/family as well as the problems and goals of the subjects. We also asked where they obtain necessary information about their condition (doctor, web). Results: 55% of the participants were 15–25 years old and 45% were between the age of 25–35 years. 72% were female. Of these, 15 live in the province of Salzburg, 15 in Upper Austria and 15 in Vorarlberg. There were 5 participants each from other provinces (Vienna, Lower Austria, Styria, Carinthia, Tyrol and Burgenland). Most young adults got their information from their doctors (50%) or from the internet (39%). 39% graduated with A-level, 27% graduated at university and 34% completed specialised job training. 78% of these young Austrians were able to earn their living; 22% were not able to work. 29% never got the chance to start working. 35% had enough support to get pregnant and to manage a family. There was a strong desire (81%) for a meeting (which was never held before in Austrian). 50% expressed willingness to help us or to run their own group. The most urgent wish of young people diagnosed with a rheumatic disorder is to be healed or to receive the ideal therapy in order to go into remission. The participants felt that there is a lack of understanding and appreciation of young people with painful chronic diseases. Some participants would like to be treated by younger rheumatologists. They feel that this would facilitate 'eye level' consultations. There is also a lack of understanding and support in schools, in civil service settings and in government agencies. A big issue mentioned was inflexible thinking, especially in job settings. Applicants with rheumatic disorders must compete with healthy individuals for forty-hour jobs. For people with a rheumatic disorder a forty-hour job is often too much, but they can do good work in a job with shorter working hours. Young people feel it is necessary to force our society and our doctors to feel responsible for the concerns of young people with rheumatism. Conclusions: Following the positive feedback the Austrian Rheumatism League organised a first meeting for those young people with rheumatism. A program of sports and relaxation in a beautiful natural setting was planned with the aim of enhancing positive, constructive thinking and well-being. We must encourage young people with rheumatic disorders to participate in the activities of the Austrian Rheumatism League, and encourage our society to give up black and white thinking. Everyone should be educated to accept and appreciate handicapped colleagues in their work setting, and to treat them as equals. Furthermore, our government should make it possible for persons with rheumatic disorders to stay at work and with their families even if they are not able to work forty hours a week. All doctors working with rheumatic patients should be familiar with their thoughts, beliefs, aims and problems in order to support them not only with drug prescriptions but also with understanding. Disclosure of Interest: None declared